2017
DOI: 10.1007/s10212-017-0332-2
|View full text |Cite
|
Sign up to set email alerts
|

The successful test taker: exploring test-taking behavior profiles through cluster analysis

Abstract: To be successful in a high-stakes testing situation is desirable for any test taker. It has been found that, beside content knowledge, test-taking behavior, such as risktaking strategies, motivation, and test anxiety, is important for test performance. The purposes of the present study were to identify and group test takers with similar patterns of test-taking behavior and to explore how these groups differ in terms of background characteristics and test performance in a high-stakes achievement test context. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 34 publications
(59 reference statements)
0
17
1
Order By: Relevance
“…Regarding effects of personality variables on cognitive test results, neither effects of test anxiety nor of risk propensity revealed significant differences, even though interactions between these characteristics and response format have been suggested by earlier research (e.g., Rowley, 1974;Benjamin et al, 1981;Crocker and Schmitt, 1987;Alnabhan, 2002;Rubio et al, 2010). As previous studies revealed effects of subjects' test anxiety and risk propensity on test scores particularly within high-stakes assessments (Segool et al, 2013;Knekta, 2017;Stenlund et al, 2018), aspects of the test situation (low-stakes) could have contributed to this finding. Given the small personal relevance of the test outcome for the pupils in the current study, test anxiety and risk propensity may not have influenced the subjects substantially in this test situation.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Regarding effects of personality variables on cognitive test results, neither effects of test anxiety nor of risk propensity revealed significant differences, even though interactions between these characteristics and response format have been suggested by earlier research (e.g., Rowley, 1974;Benjamin et al, 1981;Crocker and Schmitt, 1987;Alnabhan, 2002;Rubio et al, 2010). As previous studies revealed effects of subjects' test anxiety and risk propensity on test scores particularly within high-stakes assessments (Segool et al, 2013;Knekta, 2017;Stenlund et al, 2018), aspects of the test situation (low-stakes) could have contributed to this finding. Given the small personal relevance of the test outcome for the pupils in the current study, test anxiety and risk propensity may not have influenced the subjects substantially in this test situation.…”
Section: Discussioncontrasting
confidence: 61%
“…Numerous studies have shown a higher tendency for test takers possessing higher levels of risk propensity to guess in MC tests when they were unsure about items, while people with low risk propensity preferred to skip those questions (Alnabhan, 2002;Rubio et al, 2010;Baldiga, 2013). As the probability of guessing correctly in a MC test with eight response options is 12.5%, or even more if some distractors can be excluded, high risk-taking individuals have a significantly higher likelihood of achieving more points in MC tests than low risk-taking subjects (Rowley, 1974;Alnabhan, 2002;Rubio et al, 2010;Stenlund et al, 2018). Research showed that even when test takers were required to answer all items in a test based on MC format, persons with higher scores in the willingness to risk a penalty in a test situation outperformed those with lower risk scores (Rowley, 1974).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assessment of selfreported motivation can take place either prior to, during, or after the performance test (the economic knowledge test in the context of this paper). In the literature no clear suggestions have been made as to when test motivation should be assessed as a control variable: In some studies test motivation has been assessed immediately upon completion of a knowledge test (Knekta 2017;Ortner et al 2014); in others, an intermediate questionnaire has been completed at various points throughout the test (Stenlund et al 2018). Repeated assessment of test motivation certainly would make sense from a theoretical point of view because motivation may change during the test.…”
Section: Self-reported Motivation (Direct Indicator)mentioning
confidence: 99%
“…It is interesting to examine subscore value for males and females because these groups have for a long time been in the focus when discussing equity and fairness in society in large, and we know that they differ in several test-taking aspects, such as overall test performance, test anxiety and use of test-taking strategies (Stenlund et al, 2017(Stenlund et al, , 2018, as well as performance on constructed-response vs. multiple-choice items (Livingston and Rupp, 2004). Such group differences will show as gender bias only when these differences is unrelated to the intended test construct but still has an impact on the test result.…”
Section: Introductionmentioning
confidence: 99%